Prevention of Adhesion Following Hysterotomy Using Omentum in Rabbits - Ali, Talib Gaidan Minat; Muhamad, Sozan Ali; Jola, Mardin Omer (Sulaimani Journal for Pure and Applied Sciences, 2018)
Adhesion formation is a major source of the postoperative threaten the life of the animals. The purpose of the investigation is the effect of autologous graft by using the omentum to reduce and prevention of adhesion throughout hysterotomy in rabbits. Study was applied on 20 local breed rabbits that divided randomly into 2 groups of 10 animals each. Aseptic surgical laparotomy and hysterotomy done for all rabbits, and the omentum were used in treatment group. Postmortem and microscopic examination showed the presence of mild to severe adhesion in control group. At the 14th postoperative days, the degrees of adhesions were graded as: grade (1) in two rabbits, and (2) in the remaining two rabbits. Also at 28th post operative days, different adhesions formed and were graded as: grade (1) in two rabbits, grade 1 and 3 in one rabbit each. Conversely, in treatment group, at 14th postoperative day, 4 rabbits shown adhesion grade (2) in each 2 rabbits. While at 28th postoperative day, grade 1 adhesion was found in 3 rabbits that exhibiting moderate band of adhesion. The results of 2 run time referred that adhesion extension increased in control group with the time. The average p- value for adhesion of extension in all rabbits of treatment group was 1.50±0.577 and 1.25±0.500 at day 14th and 28th respectively. Histological examination revealed significantly high score of fibrosis with infiltration of inflammatory cells especially in control group, with slightly infiltration of inflammatory cells within muscular and serosal layers in treatment group. In conclusion, we confirmed that the using of autologous graft especially the omentum leads to somewhat reduction and prevention of adhesion during postoperative hysterotomy in rabbit model.
Keywords: Adhesion; Autologous graft; Hysterotomy; Rabbit